Secure Hill cipher modification SHC-M - Chefranov, Alexander G. (Tafford Publishing, 2008)
The secure Hill cipher strength is improved by avoiding a permutation transfer via network channels; the number of the permutation in the pseudo-random sequence is transferred instead. Pseudo-random permutation generator is used by a receiver to restore the permutation. © 2008 Atilla Elçi.
1st International Conference on Security of Information and Networks, SIN 2007 --
Keywords: Hill cipher; Permutation; Pseudo-random permutation generator